(untitled) (Research, Society and Development, 2021)
The present study aimed to explore the influence of the gut-brain axis on neuroendocrine and immunological modulation in neurological and psychiatric disorders. This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-analyzes (PRISMA) guidelines, and searches were conducted in the electronic databases PubMed and SciELO using combinations of descriptors “Gastrointestinal Microbiome”, “Neurosecretory Systems”, “Immune Response”, “Nervous System Diseases” e “Mental Disorders”. From the 144 studies generated by crossing the descriptors, 32 of them were excluded because they were duplicated in the databases, 13 because they were not related to the objectives of the review, and another 29 because they were not on eligibility criteria. Therefore, 70 studies were included in the present review. Communication between the GI tract and the CNS occurs via the neuronal, endocrine, and immunological pathways through a) the production of neurotransmitters, b) the tryptophan metabolism, c) the modulation of the immunological activity in the CNS and the SNE, d) production of short chain fatty acids, e) the production of intestinal hormones, and f) the production of branched chain amino acids.